Alcohol misuse prevalence and correlates among school adolescents from national surveys in Saint Lucia and Saint Vincent and the Grenadines. Issue 3 (4th May 2022) - Peltzer, Karl; Pengpid, Supa
Abstract : The study aimed to estimate the prevalence of alcohol use and misuse, and its associated factors, among adolescents in Saint Lucia and Saint Vincent and the Grenadines. Data from 3 847 adolescents (mean age = 14.6 years, SD = 1.7 years) that took part in national cross-sectional school surveys in 2018 in Saint Lucia, and Saint Vincent and the Grenadines were analysed. The results indicate that 42.7% of the students reported current alcohol use, 27.9% were ever drunk, and 11.4% had trouble with alcohol use. In adjusted logistic regression analyses, compared to students from Saint Lucia, students from Saint Vincent and the Granadines had higher odds of trouble from drinking. Current tobacco use and current cannabis use were highly associated with current alcohol use, ever drunk, and trouble with alcohol use; while ever use of amphetamines was associated with ever drunk. Older age was associated with current alcohol use and ever drunk, but not with trouble from drinking. Severe food insecurity and suicidal ideation were associated with trouble from alcohol use. School truancy, participation in physical fights, injury, and multiple sexual partners increased the odds, while parental support decreased the odds of current alcohol use, ever drunk, and trouble from alcohol use. In conclusion, high alcohol use and misuse have been identified that call for interventions.